An architectural lighting design to enhance individuals’ wellbeing indicators in windowless, open-plan workplace in tropical environment - Sithravel, Ratnakala (2018)
There is a need to identify supportive architectural lighting design concepts and conditions to enhance dayshift individuals’ psychophysiological wellbeing indicators (IPWI), in a windowless open-plan workplace (WOPW) in tropical Malaysia. Studies from seasonal climates have evidenced the advantages of dynamic architectural lighting over constant (regular) lighting in enhancing IPWI especially in workplace with less natural daylight contribution. However, this has not been investigated in tropical Malaysia as yet. Hence, this thesis proposes the development of Integrated Tropical Architectural Lighting Design (ITALD) framework, to justify the need to develop supportive, dynamic architectural lighting configurations for WOPW in tropical Malaysia. For this purpose, an exploratory experimental study (mixed-group design with 45 healthy postgraduate males) was initiated in a computer laboratory in Universiti Putra Malaysia to mimic a realistic WOPW. The immediate impact of a 2-hour morning exposure to overhead white LED (6500 K) ambient lighting on a number of IPWI such as urinary 6-sulfatoxymelatonin (aMT6s), alertness, positive affect, negative affect, visual comfort, cognitive and visual task performances were investigated. A few lighting configurations were also tested to identify potential threshold values and patterns that were more supportive of the morning boosting effect in tropical Malaysia. The light-settings included constant (500constant500 lx) versus dynamic lighting with horizontal illuminance in decreasing oscillation (‘500decreasing to250 lx’, ‘750decreasing to500 lx’, ‘1000decreasing to500 lx’), and increasing oscillation (‘250increasing to500 lx’, ‘500increasing to750 lx’, ‘500increasing to1000 lx’). Results revealed each light-setting immediately impacted the measured indicators either positively or negatively. Not all of the light-settings contributed towards better morning boosting effect when compared to ‘control’ (visit 1: 500constant500 lx). Only two specific configurations of dynamic lighting in increasing oscillation were identified as potentially more supportive than ‘control’; while dynamic lighting in decreasing oscillation and follow-up constant lighting were less supportive. With illuminance-and-oscillation dependent responses, this thesis recommends oscillation effect as an additional lighting factor. It influenced the direction of the immediate impact and defined a supportive, dynamic architectural lighting pattern. The two supportive light-settings were ‘500increased to750 lx’ and ‘500increased to1000 lx’. They contributed towards a better morning boosting effect than ‘control’ as they supported most of the measured indicators. They therapeutically suppressed urinary aMT6s, improved alertness, cognitive task performance, positive affect, and visual comfort. These potential light-settings established a preliminary groundwork for defining supportive, dynamic architectural lighting configurations for a morning worktime period in WOPW in tropical Malaysia. Interestingly, an increasing oscillation lighting pattern was observed more beneficial in tropical Malaysia; while a reverse pattern (decreasing oscillation) was specified for the morning boosting effect by the ‘human rhythmic’ protocol developed by studies from the Netherlands. These findings provided evidence that a supportive, dynamic architectural lighting has potentials to play an active role in enhancing IPWI during worktime, and act as an environmental therapeutic solution in minimizing light-induced circadian disruption in WOPW in tropical Malaysia. It could subsequently optimize work productivity; contribute towards better human capital performance, and positively impact an organization and the country’s sustainable economic growth. Further investigations are recommended to develop the ITALD framework.